Short communication. Sequence of msp1alpha gene of Anaplasma marginale Havana isolate and expression in eukaryotic cells - Corona, B.; Minet, C.; Albina, E.; Vega, A.; Martínez, S. (Spanish Journal of Agricultural Research, 2005)
Bovine anaplasmosis is a disease of worldwide economic importance caused by the rickettsia Anaplasma marginale. Several major surface proteins with conserved gene sequences have been examined as potential candidates for vaccines. One of these proteins, MSP1a, is expressed from the single copy msp1alpha gene. The molecular weight of MSP1a varies among the geographic isolates of A. marginale because of a varying number of tandem repeated peptides of 28-29 amino acids. In the present study, the sequence of the msp1alpha gene of Anaplasma marginale Havana isolate was determined, with a size of 2,043 kb, demonstrating the presence of five tandem repeated regions. This gene was cloned into the eukaryotic expression vector pCIneo, transfected in COS-7 cells and expression verified by immunofluorescence. These data provide a basis for an immunization strategy using the msp1alpha gene in DNA immunization containing single or multiple genes encoding major surface proteins of A. marginale.